Graphitized carbon as an efficient mesoporous layer for unitized regenerative fuel cells. (26th October 2016) - Sadhasivam, T.; Roh, Sung-Hee; Kim, Tae-Ho; Park, Kyung-Won; Jung, Ho-Young
Abstract: To enhance the electrochemical performance of membrane electrode assemblies (MEAs) for unitized regenerative fuel cells (URFCs), we prepared and introduced graphitized-carbon (Gr-carbon) of high crystallinity as a mesoporous layer (MPL) in MEAs. The round-trip energy conversion efficiencies (εRT (%)) of non-MPL, typical amorphous-carbon (Am-carbon) MPL and Gr-carbon MPL containing MEAs at the current density of 1 A cm −2 were 36.6, 41.8, and 43.8, respectively. The overall round trip energy efficiency was considerably higher for the graphitized form of mesoporous carbon. For Gr-carbon, a high stability of the round-trip energy conversion efficiency was achieved even after 20 th cycles (42.3%) owing to the enhanced electrical conductivity and high crystallinity of Gr-carbon after thermal treatment. Therefore, Gr-carbon considerably enhances the ORR and OER performances and prevents carbon corrosion and surface oxidation during the fuel cell and water electrolyzer modes in the URFC system. Highlights: Gr-carbon is a promising MPL material than Am-carbon for URFC applications. Higher electrical conductivity and corrosion resistivity attributed to Gr-carbon. The εRT of Gr-carbon MPL (43.8) is considerably higher than the non-MPL (36.6). The rate of oxidation with Am-carbon is significantly higher than with Gr-carbon. Higher cycling stability was exhibited by the MEA composed of a Gr-carbon MPL.